Efficacy of prophylactic antibiotics in the adjuvant treatment of alcohol-related liver disease (ALD): A systematic review and meta-analysisProphylactic antibiotics in ALD - Xiuyan Wang; Endian Zheng; Haoyue Sun; Beibei Xu; Liang Zheng; Yi Huang (Annals of Hepatology)
Introduction and Objectives: This research aims to evaluate the efficacy and safety of prophylactic antibiotics in patients with alcohol-related liver disease (ALD). Materials and Methods: We systematically searched databases including PubMed, Embase, Cochrane, and Web of Science up to October 2023. Our scope encompassed the influence of prophylactic antibiotics on all-cause mortality, infection, variceal bleeding, hepatic encephalopathy (HE), hepatorenal syndrome (HRS), adverse events (AE), fungal infection, clostridioides difficile infection (CDI), and multidrug-resistant (MDR) bacterial infection. Additionally, total bilirubin, creatinine, platelet counts, and plasma endotoxin levels were also analyzed. Results: After comprehensive selection, 10 studies with 974 participants were included for further analysis. The study demonstrated that prophylactic antibiotic therapy was associated with reductions in infection rates, HE incidence, variceal bleeding, and all-cause mortality. The treatment did not increase the incidence of AE, fungal infection, and CDI, but it did raise the MDR bacteria infection rate. The analysis revealed no significant protective effect of antibiotic prophylaxis on total bilirubin and creatinine levels. Furthermore, the administration of antibiotics led to marginal increases in platelet counts, a minor reduction in endotoxin concentrations, and a subtle enhancement in HRS; however, these changes did not reach statistical significance. Conclusions: Prophylactic antibiotic therapy was an effective and safe treatment for advanced ALD. To mitigate the risk of MDR bacterial infections, a strategy of selective intestinal decontamination could be advisable. Future investigations should prioritize varied ALD patient populations with extended follow-up periods and assorted antibiotic regimens to solidify the efficacy and safety of ALD treatments.